Validity and reliability of the Smartphone Craving Scale: modifying and adaptation of the Penn Alcohol Craving Scale to the Turkish culture as Smartphone Craving Scale - Savci, Mustafa (Cumhuriyet Univ Tip Fak Psikiyatri Anabilim Dali, 2019)
Objective: The aim of this study was to develop the Smartphone Craving Scale (SCS). In accordance with this general purpose, the Penn Alcohol Craving Scale (PACS) was modified to Turkish as a SCS. In other words, SCS was developed by using PACS items. Methods: This study was carried out on 429 university students (256 females and 173 males) in five different samples. The measures used included the Smartphone Craving Scale (SCS), Smartphone Addiction Scale-Short Version (SAS-SV), Brief Self-Control Scale (BSCS), and Personal Information Form. The structural validity of SCS was investigated with Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and criterion validity. The reliability of the SCS was evaluated using test-retest method, Cronbach alpha internal consistency reliability coefficient and corrected item total correlation coefficients. Results: As a result of EFA, SCS was found to have a single-factor structure. This structure explains 53.48% of total variance. This single-factor construct was tested with CFA. As a result of CFA, the single-factor structure of the SCS was confirmed in two different samples (chi(2)=5.14, df=5, chi(2)/df=0.399, RMSEA=0.016, GFI=0.98, AGFI=0.94, CFI=0.99, IFI=0.99 and TLI (NNFI)=0.99 and chi(2)=14.21, df=5, chi(2)/df=2.843, RMSEA=0.123, GFI=0.96, AGFI=0.88, CFI=0.95, IFI=0.95 and TLI (NNFI)=0.90]. Criterion validity of the SCS was evaluated with smartphone addiction, self-discipline, impulsive-ness, daily smartphone use duration, smartphone use history and frequency of checking smartphone in day. In the criterion valid analysis, the SCS was found to be related to the expected direction with these structures. Finally, reliability analysis of the SCS shows that the scale is reliable (test-retest reliability coefficient=0.79 and Cronbach's a internal consistency reliability coefficients=0.77, 0.78 and 0.77). Conclusion: When the analyzes of the validity and reliability of the SCS are evaluated as a whole, it can be said that SCS is a valid and reliable scale that measures smartphone craving.
Akilli telefon aşerme ölçeğinin geçerliliği ve güvenilirliği: Penn alkol aşerme ölçeğinin türk kültürüne akilli telefon aşerme ölçeği olarak değiştirilmesi ve uyarlamasi
Keywords: Smartphone; smartphone addiction; craving; smartphone craving